2012
DOI: 10.1007/s00221-012-3234-1
|View full text |Cite
|
Sign up to set email alerts
|

Negative priming for target selection with saccadic eye movements

Abstract: We conducted a series of experiments to determine whether negative priming is used in the process of target selection for a saccadic eye movement. The key questions addressed the circumstances in which the negative priming of an object takes place, and the distinction between spatial and object-based effects. Experiment 1 revealed that after fixating a target (cricket ball) amongst an array of semantically related distracters, saccadic eye movements in a subsequent display were faster to the target than to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…This is not to diminish the role that perceptual processing demands of the task can play in the location repetition effects. The distractor processing demands or visuospatial context (e.g., Donovan, Crawford, & Litchfield, 2012; Geyer et al, 2007; Gökce et al, 2013; Hilchey et al, 2019; Hommel, 2007; Jiang, 2018; Wang & Klein, 2010), feature repetition (e.g., Campana & Casco, 2009; Christie & Klein, 2001; Hommel, 1998; Milliken et al, 2000; Pratt & Abrams, 1999), and also search difficulty (Kruijne & Meeter, 2016) can alter location repetition effects. However, this article makes it clear that the reason(s) for any such spatial bias(es) in target–target paradigms cannot be attributed generally to differences in the amount of attention that is required to the target, independent of the responses that were required to it.…”
Section: Discussionmentioning
confidence: 99%
“…This is not to diminish the role that perceptual processing demands of the task can play in the location repetition effects. The distractor processing demands or visuospatial context (e.g., Donovan, Crawford, & Litchfield, 2012; Geyer et al, 2007; Gökce et al, 2013; Hilchey et al, 2019; Hommel, 2007; Jiang, 2018; Wang & Klein, 2010), feature repetition (e.g., Campana & Casco, 2009; Christie & Klein, 2001; Hommel, 1998; Milliken et al, 2000; Pratt & Abrams, 1999), and also search difficulty (Kruijne & Meeter, 2016) can alter location repetition effects. However, this article makes it clear that the reason(s) for any such spatial bias(es) in target–target paradigms cannot be attributed generally to differences in the amount of attention that is required to the target, independent of the responses that were required to it.…”
Section: Discussionmentioning
confidence: 99%
“…Explanatory mechanisms of the well-utilised anti-saccade task (AST), has appealed to the concept of inhibitory control together with working memory (Unsworth et al 2022 ; Crawford et al 2011 ), but there appears to be a clear dissociation in relation to the Inhibition of a Recent Distractor (IRD), a task that is more akin to a spatial negative priming task (Crawford et al 2005a ; Donovan et al 2012 ). The AST requires the inhibition of a natural pull towards a sudden target onset, and gaze aversion to the opposite side of the screen (Hallet, 1978).…”
Section: Inhibition Of Visual Distractorsmentioning
confidence: 99%
“…It is this latter process that appears to be more directly relevant to the reading task, where target words are selected in each fixation from competing, alternative words. Therefore in this study we have turned to the inhibition of recent distractor (IRD) previously used by Crawford et al (2005) and Donovan et al (2012). We contrast performance in the recent distractor task and the conventional antisaccade task in dyslexic and normal readers.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, our previous research has clearly demonstrated that the antisaccade task is not sufficient to generate the “spatial inhibition at the location of distractor” that we find in the recent distractor task (Crawford et al, 2005). Donovan et al (2012) demonstrated that the presence of distractor in the probe display as well as the prime display is also require for object inhibition (Donovan et al, 2012). Spatial inhibition at the location of a distractor is enhanced in the presence of a competing target.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation